Konsep Tuhan Nietzsche dan Pengaruhnya terhadap Pemikiran Liberal - Mohammad Muslih; Haryanto . (Universitas Darussalam Gontor, 2018)
This article departs from the Freidrich W. Nietzsche's issue on misunderstanding of God. He ‎thought that God was the product of poets (human engineering results). Thus, disassembling the order of truth existing in modern era with his adagium “God Is Dead.” This provides a new discourse of thought, which ‎arises from an anti-God view i.e. “anti-Christ” and hatred of absolutism which result the ‎truth relativism. Nietzsche's ideas greatly influenced the mainstream of liberalist; among them are the students of State Islamic university of Indonesia who declare an ignorance expression of Islam is not only the true religion. More over their claim about the God-freezone institution when welcoming new students. It is surely inappropriate exclamation cames from Muslim students in the country with majority Muslim in the world. Their attitude is the result of a thought that has been affected with the thoughts of Friedrich Wilhm Nietzsche